2017
DOI: 10.1111/trf.14196
|View full text |Cite
|
Sign up to set email alerts
|

Severe hemolysis after plasma transfusion in a neonate with necrotizing enterocolitis, Clostridium perfringens infection, and red blood cell T‐polyagglutination

Abstract: Anti-T antibodies are unlikely to be the etiologic factor for the hemolytic reactions observed in infants with NEC and T activation. Massive RBC desialylation and the direct action of bacterial toxins are more probable causes. Strict avoidance of plasma-containing blood products does not seem justified in these infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…To gain a better understanding of this patient's outcome, they performed a prospective study to more closely examine the relationship between NEC, T‐activation, and hemolysis in patients in the neonatal intensive care unit (NICU). As stated in their introduction, “the causal relationship between T‐activation and hemolysis has been called into question by many clinicians and serologists.” Their work adds more information to this provocative topic and also presents prospective data with more detailed laboratory testing than many previous studies.…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…To gain a better understanding of this patient's outcome, they performed a prospective study to more closely examine the relationship between NEC, T‐activation, and hemolysis in patients in the neonatal intensive care unit (NICU). As stated in their introduction, “the causal relationship between T‐activation and hemolysis has been called into question by many clinicians and serologists.” Their work adds more information to this provocative topic and also presents prospective data with more detailed laboratory testing than many previous studies.…”
mentioning
confidence: 95%
“…DTT treatment showed that the anti‐T was IgM and the titer at 4°C was 8. No hemolysis of neuraminidase‐treated RBCs was observed in vitro with a serum sample from the plasma donor …”
mentioning
confidence: 99%
See 3 more Smart Citations